Membangun Restoran Sukses di Kota Surabaya: Studi Kelayakan Bisnis yang Komprehensif - Aurora Oktaviani putri Hidayat; Dwi Rahmawati; Dwi Astuti (CV. ITTC INDONESIA, 2025)
This study aims to analyze the feasibility of establishing a restaurant in Surabaya, one of the largest cities in Indonesia with significant market potential. The research investigates several key aspects including market potential, technical considerations, financial projections, and environmental factors. The findings reveal a promising market for new restaurants in Surabaya, but emphasize the importance of thorough planning in technical, financial, and environmental aspects to ensure business success. Recommendations include increasing government support, strengthening local wisdom, fostering collaboration among stakeholders, and enhancing public awareness of sustainable business practices.